1997
DOI: 10.1074/jbc.272.44.27936
|View full text |Cite
|
Sign up to set email alerts
|

Binding Sites and Binding Properties of Binary and Ternary Complexes of Insulin-like Growth Factor-II (IGF-II), IGF-binding Protein-3, and Acid-labile Subunit

Abstract: We have examined regions of rat IGF-binding protein-3 (IGFBP-3) important for complex formations using two kinds of deletion mutants, three kinds of chimera molecules between rat IGFBP-3 and rat IGFBP-2, and a synthetic peptide (41 residues, Glu 52 -Ala 92 ) derived from rat IGFBP-3. Solid-phase binding assays using 96-well microtiter plates were designed to quantitate the relative binding affinities. It was found that not only the IGFBP-3 derivatives with the amino-terminal, cysteine-rich domain (N domain) bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 32 publications
2
44
1
Order By: Relevance
“…As the region 201-218 of the IGFBP-3 and -5 has been implicated in these interactions this suggests that IGFs may have the potential to disrupt IGFBP binding to these proteins/structures and this may in turn have important biological consequences. In terms of the recognition characteristics in this molecular axis it is perhaps of special interest that the 85 kDa glycoprotein ALS (Baxter 1988) is also believed to interact with IGFBP-3 and -5 via the 201-218 region (Hashimoto et al 1997, Firth et al 1998, Twigg et al 1998. However it has been clearly demonstrated that prior engagement…”
Section: Discussionmentioning
confidence: 99%
“…As the region 201-218 of the IGFBP-3 and -5 has been implicated in these interactions this suggests that IGFs may have the potential to disrupt IGFBP binding to these proteins/structures and this may in turn have important biological consequences. In terms of the recognition characteristics in this molecular axis it is perhaps of special interest that the 85 kDa glycoprotein ALS (Baxter 1988) is also believed to interact with IGFBP-3 and -5 via the 201-218 region (Hashimoto et al 1997, Firth et al 1998, Twigg et al 1998. However it has been clearly demonstrated that prior engagement…”
Section: Discussionmentioning
confidence: 99%
“…The amino-terminal domains of IGFBPs 1-6 (usually incorporating all 12 cysteine residues) have been reported to bind IGF (8,9,26,(37)(38)(39)(40). Interestingly, the central linker region appears to contribute to the structural integrity and hence the IGF binding potential of these amino-terminal fragments.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of sequence alignments, exon coding regions (28), and naturally occurring IGFBP fragments (6,7,10,17,18,26,28), discrete modules of the native protein encompassing the amino-terminal domain (amino acid residues 1-93, 1-104, 1-132, and 1-185) and carboxyl-terminal domain (amino acid residues 96 -279, 96 -284, 136 -279, and 182-284) of bIGFBP-2 were recombinantly expressed and investigated using BIAcore analysis (Fig. 1).…”
Section: Igfsmentioning
confidence: 99%
“…Others have previously ruled out the central domain heparin binding motifs as functional heparin binding sites, on the basis of studies with the full-length IGFBP-5 protein that involved both competitive binding studies with synthetic peptides from these regions (Arai et al 1994) and amino acid substitutions at these putative heparin binding motifs (Arai et al 1996), which suggested that the C-terminal site alone is active. Domain switching to create chimeric IGFBP proteins has previously been adopted by other groups in order to ascertain which domain/s of IGFBP-3 and -5 are involved in binding to a liver-derived glycoprotein known as the acid-labile subunit (ALS) (Hashimoto et al 1997, Twigg et al 1998. Using this approach, it was demonstrated that the homologous stretch of basic amino acids in the C-terminal domains of and is necessary for ternary complex formation with ALS and IGFs.…”
Section: Introductionmentioning
confidence: 99%